Dinâmica migratória e avaliação dos quesitos censitários sobre migrações internas e internacionais em Moçambique: uma análise a partir do censo 2017 - Ibraimo, Mussagy Ismael Savai (2022)
Migratory movements are part of people's lives, presenting great complexity in their characteristics, measurement techniques, causes and effects. As the demographic census is the main source of data on migratory processes in Mozambique, the objective of this work was to evaluate the quality of migration measurement question, using microdata from the 2017 census, in order to assist in the analysis of trends. and migratory dynamics, which are essential for public policy planning. Consistency analyzes of the migration measurement question were performed, where it was found that only the fixed date item showed inconsistency in the codes of the geographic units of the level below the province, which determined the choice of this as the unit of analysis. Direct migration techniques were applied to calculate measures such as the number of emigrants, immigrants, balance of migration, net migration rates and migratory efficiency index, which helped in the analysis of internal and international migratory trends and dynamics. The results obtained showed that the profile of the migrants is predominantly of young people of working age, being single or in a marital union, and presenting a low to medium level of schooling. There was a similar trend between recent and five-year migrations and a reduction in international immigration, associated with issues of insecurity, caused by the resurgence of political-military conflict in the period from 2013 to 2019 in the Central region of the country. In terms of spatial distribution, there was a greater concentration of migratory flows between provinces of the same region (intra-regional), which may be the result of the development registered locally as a result of the investments made, with emphasis on the megaprojects in the extractive industry in the regions Center and North. In this way, it is concluded that socioeconomic, political and natural disasters may be among those that most influenced the migratory dynamics in Mozambique.